Oncological Outcomes of Patients With Different Pathological Features of pT3a Renal Tumor: A Systematic Review and Quantitative Synthesis - Guo, Pengju; Wang, Yongxing; Han, Yili; Wei, Dechao; Zhao, Jiahui; Li, Mingchuan; Jiang, Yongguang; Luo, Yong (Frontiers in Oncology, 2021)
Purpose: To identify the discrepancy of oncological outcomes for different pT3a renal tumor invasion patterns and pathological features. Methods: Relevant studies were identified by searching the PubMed, Cochrane library, Embase, and Web of Science. Cancer-specific survival (CSS) was selected as the endpoint. Pooled hazard ratio (HR) and 95% confidence interval (CI) extracted from multivariate cox models were evaluated to identify the hazard association. Results: A total of 22 studies enrolled 12384 patients were included for quantitative synthesis. Sinus fat invasion (SFI) + perinephric fat invasion (PFI) was associated with inferior CSS compared to SFI only (HR 1.97, 95% CI: 1.13-3.42, p=0.02). The comparable CSS was observed between SFI and PFI (HR 0.92, 95% CI: 0.69-1.23, p=0.57). SFI±PFI showed inferior CSS compared to PFI only (HR 1.81, 95% CI: 1.33-2.47, p=0.0002). The presence of pelvicalyceal system invasion significantly increased the risk of cancer-specific mortality (HR 1.91, 95% CI: 1.33-2.75, p=0.0005). Renal vein invasion (RVI) indicated poor oncological outcomes with respect to CSS (HR 1.45, 95% CI: 1.15-1.82, p=0.002). The concomitance of RVI and fat invasion (FI) significantly increased the risk of deterioration of CSS compared to RVI or FI (HR 2.13, 95% CI: 1.52-2.99, p<0.0001). Multiple patterns invasion translated into a significant decreased CSS (HR 1.77, 95% CI: 1.49-2.09, p<0.0001). Aggressive tumor behavior, including lymph node involvement (HR 1.71, 95% CI: 1.17-2.50, p=0.006), distant metastases (HR 3.36, 95% CI: 2.88-3.91, p<0.00001), sarcomatoid differentiation (HR 2.09, 95% CI: 1.78-2.46, p<0.0001), necrosis (HR 1.96, 95% CI: 1.54-2.49, p<0.0001), Fuhrman grade III or IV (HR 2.70, 95% CI: 2.18-3.34, p<0.0001), positive margin (HR 7.61, 95% CI: 4.12-14.04, p<0.0001), and size >7cm (HR 1.77, 95% CI: 1.46-2.15, p<0.0001) were the predictors of inferior CSS. The lymphovascular invasion (HR 1.11, 95% CI: 0.69-1.80, p=0.67) were indolent in terms of CSS. Conclusion: We identified the heterogeneous classification of pT3a renal tumor in the current TNM staging system and aggressive pathological features of CSS. A precise risk grade of CSS for different invasion patterns including comprehensive combinations may be useful for the further refinements of the TNM system.